Magnetic double-tartaric bridging mono-lanthanide substituted phosphotungstates with photochromic and switchable luminescence properties. Issue 23 (18th May 2016) - Ma, Pengtao; Hu, Feng; Wan, Rong; Huo, Yu; Zhang, Dongdi; Niu, Jingyang; Wang, Jingping
Abstract : A series of inorganic–organic hybrid multifunctional crystalline materials constructed using double-tartaric bridging mono-lanthanide substituted phosphotungstates display reversible photochromic, switchable luminescence, and magnetic properties. Abstract : A series of inorganic–organic hybrid double-tartaric bridging mono-lanthanide substituted phosphotungstates with a general formula of [N(CH3 )4 ]6 K3 H7 [Ln(C4 H2 O6 )(α-PW11 O39 )]2 ·27H2 O (Ln = Dy for1Dy, Er for2Er, and Yb for3Yb ) have been synthesized by the reactions of K14 [P2 W19 O69 (H2 O)]·24H2 O and LnCl3 ·6H2 O in the presence of tartaric acid and tetramethyl ammonium counterions in an aqueous medium. Crystal structure analyses reveal that1Dy–3Yb are isomorphic and are all built from two mono-lanthanide substituted Keggin polyoxoanion fragments joined together by two tartaric ligands.1Dy–3Yb exhibit reversible photochromism and they can change from white (for1Dy and3Yb ) or pink (for2Er ) to blue upon UV irradiation and then their colors gradually recover in the dark for about five days. The solid-state photoluminescence spectra of1Dy–3Yb display their characteristic emissions of lanthanide components based on their 4f–4f transitions. Moreover, the fluorescence of1Dy displays an effectively switchable behaviour when exposed to UV light, the intensity of the emission band at 573 nm gradually weakens as the irradiation time increases and the intensity drops to 2.4% of the original intensity after 30 minutes. It is noteworthy that the frequency dependence of the ac-susceptibility was found for1Dy, suggesting a typical single-molecule magnet (SMM) behavior with an energy barrier of 20 K.